Analysis of Work Motivation and Work Discipline on Employee Job Satisfaction PT. Pilar Indo Abadi Surabaya - Sutoyo, Sutoyo; Koen Irianto Uripan (SEAN Institute, 2026)
This study aims to determine the effect of Work Motivation and Work Discipline on Employee Job Satisfaction at PT. Pilar Indo Abadi. The population in this study was all employees of PT. Pilar Indo Abadi Surabaya, using a saturated sample method, resulting in a sample size of 60 employees of PT Pilar Indo Abadi Surabaya. To prove the hypothesis, the test used was Partial Least Square. Based on the results of the study, it was found that Work Motivation has a positive effect on Job Satisfaction and Work Discipline has a positive effect on Job Satisfaction.